Comparison between experimental methods and computer simulation in studying steady state thermoelectric generation - Liew, Yuan Jie (Nanyang Technological University, 2024)
Thermoelectric generator (TEG) is a solid-state device that directly converts heat into electrical energy and vice versa via the amalgamation of Peltier, Joule and Thomson effects. These devices are widely used in waste heat recovery. At first, this study evaluates the performance of a TEG using Wolfram Mathematica. The modelling and simulation are performed through deriving the governing equations of steady state thermoelectric generation, inputting the relevant parameters and then comparing the simulation outputs with experimental data used as the control data. Using analytical solution approach, the model solves for values of efficiency, output power and temperature difference in the TEG, using inputted parameters from the experimental data, namely input power and mean temperature. The analytical solution derived shows satisfactory results as compared to experimental data but only valid for a limited range of Δ from 150ºC to 250ºC. The simulations predict the performance of the TEG at Δ =234° with an output power of 7.27 W, and the efficiency of 5.35% at Δ =216° . Meanwhile, the reliability of experimental data is influenced possible underperformance of the TEG apparatus. From the experimental observations, maximum output power and efficiency to be 0.42 W and 0.76% respectively. These values are found to be lower as compared to simulation results. Through this study, several research outcomes were achieved: firstly, understanding the working principles of a TEG through both experimental observations and theoretical governing equations. Secondly, measuring performance parameters of a TEG such as power output and efficiency and understanding which parameters have the greatest effect on TEG performance such as hot and cold junction temperatures. Lastly, understanding the process and limitations of simulation approaches for modelling a TEG.